Approximated Mathematical Analysis Methods of Guard-Channel-Based Call Admission Control in Cellular Networks - Cruz-Pérez, Felipe A.; Toledo-Marín, Ricardo; Hernández-Valdez, Genaro (IntechOpen, 2011)
None